Gone or Go On? The Existence of Hybrid Events As Urban Tourism Strategy - Sari, Yulita Kusuma (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2023)
As the name might suggest, a hybrid event is a mix of live and virtual events. Starting its popularity in the middle of 2020, it emerged as a response and survival strategy for the creative community and the tourism industry during the COVID-19 pandemic, especially in urban areas. This form of adaptation was acknowledged several months after the virus outbreaks. Following the title, hybrid events during the pandemic may be seen merely as a non-permanent solution or a novelty for further development. This research believes that the transformation influences four fundamental aspects—technology, institution, people, and environment. Those aspects are essential in shaping a new form in the global era. Based on the ideas of transformation in the globalization era and tourist experience theory, the discussion focused on the people involved in the events industry, how the hybrid events have been carried out to date, and how they relate to urban tourism. This research aims to discover the existence of hybrid events for urban tourism years after the COVID-19 pandemic. The results highlight how hybrid events during the COVID-19 pandemic significantly impact the tourist movement and directly affect the tourism industry. Unlike the conventional event, the participant did not gain the utmost tourism experience in the urban destination. Following that, some patterns have been found in the hybrid event. Those patterns indicate the existence and hybrid event’s potential for further development.